PENCIPTAAN KARYA TEATER BONEKA “POPPY-UTOPIA” - ida bagus, nanda adi naya; Widnyana, I Kadek; Wicaksana, I Dewa Ketut (JURNAL DAMAR PEDALANGAN, 2025)
“Poppy-Utopia” is a puppet theater performance that offers a profound reflection on life through the unique perspective of a dog named Poppy. This production delves into various social issues, particularly the negative stigma often directed at dogs within cultural contexts, utilizing an artistic approach that integrates narrative, visual elements, and puppetry techniques. The creative process is guided by I Wayan Dibia's five-stage method, encompassing Ngawirasa (inspiration from dog training and cultural stigma), Ngawacak (exploration of literature, Balinese epics, and visual arts), Ngarencana (conceptualizing a theater design combining human theater, animation, and minimalist visuals), Ngawangun (script execution, rehearsals, and illustration creation), and Ngebah (final performance with integrated artistic elements). Through a compelling storyline, nuanced characters, and innovative visuals, Poppy-Utopia delivers an emotionally engaging and reflective theatrical experience. The performance invites audiences not only to be entertained but also to reflect on themes of loyalty, struggle, and the importance of fostering harmonious relationships between humans, animals, and nature.